Health and leisure time physical activity promotion through exergaming for individulas with spinal cord injury / Maziah Mat Rosly - Maziah , Mat Rosly (2018)
Individuals with spinal cord injury (SCI) face challenges in maintaining leisure time physical activity (LTPA) participation and adherence to exercise. LTPA is important for improving fitness, quality of life and cardiometabolic profiles. However, epidemiological data among community-dwelling SCI revealed low participation (29-53%) in “dosepotent” LTPA, defined as aerobic exercise of moderate-vigorous intensity for health benefits. The studies provided evidence that participation in LTPA is related to barriers due to wheelchair dependency. Recurrent themes often cited include expensive equipment, boring and monotonous exercises, issues with transportation and the inaccessibility of training facilities. The Physical Activity Scale for Individuals with Physical Disabilities and the Barriers to Exercise Scale questionnaires were used to collect descriptive information on LTPA and the associated barriers to exercise. Adaptation and translation of these questionnaires to fit Malaysian cultural competency were proceeded with validation of its Malaysian rendition (Chapter 3). Dose-potent LTPA participation (Chapter 4), assessed within the scenario of a non-western culture and Asian developing country revealed low participation (27%). The majority of respondents came from a lower socioeconomic bracket, 70% with a monthly household income of less than RM2500; including 27% of them earning less than RM1000. The top three barriers reported were costly exercise equipment (54%), pain while exercising (37%) and no access to facilities (36%). Significant predictors for dose-potent exercise participation were age more than 35 years old, ethnicity, reporting transportation difficulties and health concerns. A systematic review (Chapter 4) explored the exercise alternative, “exergaming” (a combination of active bodily movements with video gaming) for iv population with neurological disabilities. The review concluded that exergaming could provide moderate or vigorous intensity aerobic exercise as recommended by health guidelines. An exergaming pilot study (Chapter 4) in adult SCI demonstrated its feasibility to produce adequate “dose-potency” prescribed for health benefits. There were significant physiological differences (p<0.05) in the metabolic responses while exergaming using Move Tennis (unilateral, dominant upper limb movements) against Move Boxing and Move Gladiator Duel (bilateral upper limb movements). Move Kayaking was adapted for use among a study sample with SCI. In Chapter 4, physiological responses between Move Boxing and heavy-bag boxing revealed no significant differences (p>0.05), with only small to moderate effect sizes (Cohen’s d, 0.02-0.49). However, Move Boxing was perceived to be more enjoyable, easier to assemble, comfortable to use, motivating for longer duration and for home training. The final study (Chapter 5) assessed three different exercise types (Move Boxing, Move Kayaking and arm cranking) that were conducted within similar training zones to compare the ratings of perceived exertion (RPE) and enjoyment. All three exercise types achieved vigorous intensity according to the peak heart rate. Move Boxing was the most significantly (p<0.05) enjoyable exercise compared to Move Kayaking and arm cranking. Exergaming’s RPE was significantly (p<0.05) more than arm cranking owing to the complex arm movements during gameplay. Move Boxing reported higher RPE but was significantly more enjoyable than arm cranking.